An analysis of myotonia in paramyotonia congenita - Burke, David (1974)
In two subjects with paramyotonia congenita myotonic delay in muscle relaxation, recorded electromyographically and with a displacement transducer, was found to increase with repeated forceful contractions. Myotonia was elicited readily in warm temperatures, was initially aggravated by cooling, but was invariably lost as muscle fatigue developed. The EMG evidence of myotonia usually subsided before complete muscle relaxation had occurred, suggesting that a defect of the contractile mechanism was present over and above any defect at membrane level.